Intestinal intussusception in infants: Interest of ultrasound-guided hydrostatic reduction - Maskaoui Nasser (EDP Sciences, 2021)
Ultrasound-guided hydrostatic reduction of acute intussusception is a nonoperative technique, simple, performed under ultrasound guidance without risk of irradiation. Purpose: Our study aimed to evaluate the efficiency and utility of Ultrasound-guided hydrostatic reduction in the management of infant intussusception. Material and Methods: We conducted a retrospective study of cases of intussusception in infants (1-24 months) treated in the pediatric surgical emergency service of Rabat children’s Hospital during the period 2016-2020. Of the 135 cases collected during the study, 109 patients received ultrasound-guided hydrostatic reduction while 26 infants inderwent primary surgery. Results: This condition was most common in the age group (3-9 months) with 78% of cases. The sex ratio M/F was 2.29. The ileocolic type was the most encountered (56%). The complete ultrasound hydrostatic reduction was achieved for 88 infants with a success rate of 81% and an average hospitalization time of 1.4 days. 21 cases (19%) of which 16 failed hydrostatic reduction and 05 recurrences within 24 hours, were taken up by surgery with manual reduction and bowel resection for respectively 19 and 02 cases. Conclusion: Ultrasound guided hydrostatic reduction is a safe, quick and efficient method with a high success rate, a decrease in the occurrence of recurrences and complications and should be recommended first.